Using motivational interviewing to support reading motivation and engagement in secondary school pupils - Barrett, Rebecca (2020)
Around one fifth of pupils in the UK do not achieve basic reading proficiency by 15 years of age, with rate of reading progress appearing to slow for some (DfE, 2019; OECD, 2019), suggesting that some may experience challenges during secondary school. The role of reading motivation has been highlighted as key but is consistently found to decline (Clark & Teravainen-Goff, 2020). Motivational Interviewing (MI) is a person-centred approach that explicitly seeks to promote change by evoking motivations and individually guided intervention (Miller & Rollnick, 2012). Previous research exploring MI in supporting reading-related outcomes is sparse, however, with only one study finding positive outcomes. This current sought to explore how involving pupils as active collaborators in intervention, through the use of MI, could support reading motivation and engagement. A multiple case study approach was adopted with six secondary school pupils identified by their schools as disengaged and not making expected progress. Pupils engaged in five or six MI sessions, and, where possible, a pupil-teacher consultation. Data from pre- and post-intervention semi-structured interviews were analysed using Thematic Analysis (Braun & Clarke, 2006). Findings suggest that MI may be a useful tool in enhancing pupil reading motivation and engagement and facilitating wider systems-level change. Specifically, peers, computer-based reading programmes, technical reading instruction, and transition were highlighted as key influences. Limitations of the methods are considered: further research is needed to explore reading achievement outcomes and the causal nature of MI processes. Recommendations for schools, policy-makers, and Educational Psychology practice are made, with pupil participation highlighted as key to inform educational experience.